Study Of Soil Physical Properties Of Oil Palm Plants (Elaeis Guinensis Jacq) In The Labuhanbatu University Practice Area In Rantau Selatan District - Sabribal Utandi Harahap; Fitra Syawal Harahap; Hilwa Walida; Khairul Rizal (International Journal of Science and Environment (IJSE), 2024)
The physical properties of the soil that need to be considered are the problem of degradation and soil structure due to management functions so that cultivated land is not eroded and organic matter is lost quickly.This research was carried out through 2 stages of activities, namely field activities and analysis activities. Stages of field activities were carried out at the Palm Oil Plantation on the Practical Land of Labuhanbatu University, Labuhanabtu, North Sumatra Province at a height of 28 meters. The method used in this research is a free grid measurement method at a semi-detailed survey level (observation frequency of 1 sample per 500 meters). Carrying out soil sampling at up to 5 sampling points with a distance of 100 meters in the field using a random method, spread over a predetermined area based on the base map. Results of land use research withSoil texture in the Labuhanbatu University Practice Field, Labuhanbatu Regency, sandy loam, The bulk density value shows low, soil porosity is still high, the soil color looks relatively dark, and the soil water content is still relatively normal.